The Relationship Between Exclusive Breastfeeding, Occupation, Income, and Education with Stunting in Toddlers Aged 6-24 Months in Lebak Parahiang Village - Rita Ariesta; Siti Suminar; Roslina Roslina; Aminah Aminah (International Journal of Health Engineering and Technology, 2026)
Stunting is a chronic nutritional problem that affects children’s physical growth and cognitive development. Factors influencing stunting include exclusive breastfeeding practices, family income, maternal occupation, and maternal education. Optimal exclusive breastfeeding for the first six months of life has been proven to prevent stunting. However, stunting cases are still found in Lebak Parahiang Village, Leuwidamar District, thus research on these factors is necessary. To determine the relationship between exclusive breastfeeding, family income, maternal occupation, and maternal education with stunting among children aged 6–24 months in Lebak Parahiang Village in 2025. This study used a quantitative approach with an analytical observational design and a cross-sectional method. The population was all children aged 6–24 months in Lebak Parahiang Village, with 71 samples determined using the Slovin formula. Data were collected through questionnaires and anthropometric measurements. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. The results showed that most mothers practiced exclusive breastfeeding for more than six months; however, some children still experienced growth retardation. Statistical analysis revealed a significant relationship between exclusive breastfeeding, family income, maternal occupation, maternal education, and stunting (p < 0.05). Strengthening maternal education regarding the importance of exclusive breastfeeding, improving child feeding practices, and providing continuous support from health workers are recommended. Regular child growth monitoring and family-based interventions should be enhanced by health authorities and local government to reduce stunting prevalence.